Interferência das adições de água e de uréia na qualidade do leite cru refrigerado - Denise Araujo de Oliveira (2009)
he quality of dairy foods depends on the quality of raw milk. Based on that, some industries have adopted the milk payment following quality criteria, which include, besides other, protein content as one of great interest. This work evaluated the consequences of frauds related to milk adulteration by urea and water added in different concentrations. Seven raw milk samples were collected from milk cooling tank in an experimental farm at the UFMG. They were submitted to the analysis of SCC and TBC and contents of fat, protein, lactose, total solids, and solids non-fat by infra-red spectrometry. Analyses of crude protein (Kjeldahl), titratable acidity, pH, density, and stability to alizarol were also carried out. The results showed that the adulteration of milk altered the physic-chemical composition in all tested treatments in which water was added. Urea adding caused an increase in contents of protein and solids non-fat, while decreased the value of milk fat. The lactose content was not altered. It was also concluded that milk samples suspected of those frauds presenting protein content higher than 3.4%, low titratable acidity and high cryoscopic index should be tested for urea in order to confirm the suspicion.